Biochemical Studies on the Cardioprotective Effect of Squalene against Isoprenaline-induced Myocardial Infarction in Rats K - T.V., Sankar; K.H, Sabeena Farvin; R., Anandan; S.H.S., Kumar; Mathew, Suseela; P.G., Viswanathan Nair (Fishery Technology, 2025)
This study was designed to examine the cardioprotective effect of squalene against isoprenaline-induced myocardial infarction in male albino rats. Levels of diagnostic markers [troponin T, homocysteine], lipoproteins [apolipoprotein Al, apolipoprotein B, lipoprotein (a)] (in plasma), total cholesterol, lipid peroxides (in plasma and heart tissue), and endogenous non-enzymatic antioxidants [vitamin C and vitamin E] (in heart tissue) were determined. Supplementation of squalene at 2% level along with feed for 45 days significantly prevented the isoprenaline-induced elevation in the diagnostic markers in plasma of experimental group of rats. It exerted an antilipidemic action against isoprenaline-induced hypercholesterolemia by maintaining the levels of cholesterol and lipoprotein components at near normalcy. Squalene supplementation exhibited an antioxidant effect against isoprenaline-induced myocardial infarction by blocking the induction of lipid peroxidation. A tendency to prevent the isoprenaline induced reduction in the non-enzymatic antioxidants such as vitamin E and C was also observed. The results of the present study indicate that the cardioprotective effect of squalene might be ascribable to its antilipidemic, antioxidant and membrane stabilizing properties.